Tinjauan Yuridis Kewenangan Mahkamah Konstitusi Menguji Peraturan Pemerintah Pengganti Undang-Undang Terhadap Undng-Undang Dasar Republik Indonesia Tahun 1945 - Zainuri, Ahmad (JURNAL PROPERTY RIGHTS, 2014)
ABSTRACT Zainuri, Ahmad, 2014 The Juridical Review On Authority Of The Constitutional Court in order to Examine the Goverment Regulation that Replacing Constitution Of Indonesian Republic, Mini Thesis, Department Of Jurisprudence, Faculty Of Law, Kanjuruhan University Of Malang, Supervisor I Miya Savitri., S.Pd., M.Hum, Supervisor II Sulthon Miladiyanto., SH., MH. Keywords: Authority, Constitusional Court, Government Regulation to Replece Law. Objectives of the research are to find out: constitutional authority of the constitutional court to examine the government regulation to replace law, juridical implication on constitutional court to examine the government regulation to replace law. The legal research is library research, in which it is research that observes law principles, law systematic, law synchronization level, history of law, and law comparison. This research applied some approaches such us statute approach and conceptual approach. Data source of this research is secondary data that includes primary, secondary, and tertiary materials. The analysis technique on law materials was done qualitatively. After performing the research, the writer has found as follow: first , the position of government regulation to replace law after following the amendment UUD 1945 that has conformed to the Indonesian constitutional system, the presidential system, whereas materials government regulation to replace law has been organized in article 22 of UUD 1945, which have never been changed, both the government regulation to replace law and law have similarity based on its substance, but they are different based on the from and condition (time) when they ware established, so that the constitutional court has authority to examine the government regulation to replace law. It show that the constitutional court treats UUD1945 as living document, which interprets UUD 1945 in accordance with the condition at present, the base of law, taken by the constitutional court to examine the government regulation to replace law, is decision of ththe constitutional court number 138/PUU-VII/2009. The juridical implication concerning with the authority to examine the government regulation to replace law by the Constitutional Court has created some problem of law over the authority of the Indonesian Legislative Assembly, in which in accordance with UUD 1945, the Indonesian Legislative Assembly has an authority to accept or reject such the government regulation to replace law. Such law problem occurs if, in the same time the Constitutional Court to examine the government regulation to replace law, while the Indonesian Legislative Assembly is in court session in response to the government regulation to replace law.